Systemic diseases and other painful conditions in patients with temporomandibular disorders and migraine - Edwin Fernando Ruiz Contreras; Giovana Fernandes; Paula Cristina Jordani Ongaro; Leticia Bueno Campi; Daniela Aparecida Godoi Gonçalves (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Temporomandibular disorders (TMD) are a highly prevalent, painful musculoskeletal condition affecting the masticatory system, and are frequently associated with migraines (M) and other diseases. This study aimed to investigate the association between painful TMD and M with other painful conditions and systemic diseases, such as cervicalgia, body pain (BP), ear-nose-throat disorders, musculoskeletal disorders, diabetes, cardiopulmonary diseases and gastritis/peptic ulcer. Methods: This was a cross-sectional study conducted in a sample of 352 individuals. Participants were stratified into three groups according to the presence of painful TMD and M: controls [individuals free of TMD and any headache (HA)]; TMD only (presence of painful TMD, but free of any HA); and TMD+M (presence of painful TMD and M). TMD was classified according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) - Axis I. Nonspecific physical symptoms (NSPS) were assessed by RDC/TMD - Axis II. The International Classification of Headache Disorders - II criteria, second edition, were applied to identify and classify primary HA. Other painful conditions and systemic diseases were assessed by volunteers' self-report. The prevalence of all assessed conditions was higher in the TMD+M group. Multiple regression models showed that cervicalgia was associated with the TMD only group (p<0.05), whereas gender (p<0.05), cervicalgia (p<0.05), BP (p<0.05) and NSPS (p<0.05) were significantly associated with the TMD+M group. Our results suggest that individuals with a comorbidity (TMD associated with M) have a more severe condition than those presenting only painful TMD.